(untitled) - Conrad, Phillip Kottak (New York, 2010)
This book provides a carefully balanced introduction to core topics in the four subfields of general anthropology--physical anthropology, archeology, linguistics, and cultural anthropology--as well as contemporary changes in the field.
Keywords: Anthropology,Nhân chủng học; Title,Tựa đề